Evaluation Of Mathematics Learning In Elementary School Grade IV: The Importance Of Numeracy - Refiona Andika; S Hendri; M Masniladevi; Z Zuryanti (International Conference on Elementary Education, 2023)
The obligation of a teacher in improving the learning process is to compile an assessment. This study aims to describe the evaluation of the assessment of learning for class IV mathematics learning on numbers material. This research method uses a descriptive method. The subjects of this study were 14 students of grade IV elementary school consisting of 8 men and 6 women. The data in this study consisted of mid-examination questions, answer sheets, and the results of interviews with teachers and students. Based on the results of the assessment carried out, the average processed is 58. The number of students who have a score >70 is 3 students, while those who get a score ≤70 are 11 students. Based on the results of the assessment and interviews that have been carried out, mathematics learning on the number material and place values has not been mastered by students, some of the factors that cause this to happen are: 1) the learning process that still prioritizes remembering skills, so that the learning carried out has not been meaningful by students; 2) lack of application in daily life; 3) the lack of material meaning across sciences, and 4) Assessment items are generally at a low cognitive level. The main goal of learning mathematics is to develop problem-solving skills. For this goal to be achieved, the process of learning mathematics must be to relate to everyday life and also across sciences. This mathematics learning process is called numeracy.